Southeast Asian Islam: plurality, tolerance and change - Cederroth, Sven (NIAS nytt, 2004)
Cederroth, Sven: Plurality, tolerance and change in Southeast Asian Islam Bajunid, Omar Farouk: Islam in Malaysia : between rhetoric and reality Hassan, Sharifah Zaleha Syed: Islam, state and civil society in Malaysia : the case of the Al Arqam Frisk, Sylva: Claiming religious space : Malay women and the transformation of rituals in the urban context Azra, Azyumardi: Indonesian Islam, election politics and beyond Morville, Kristian: A religiously based institutionalization of democracy Hellman, Jörgen: Ramadan fasting at a pesantrén in West Java Cederroth, Sven: Return of the birds : images of a remarkable mosque in Lombok Trankell, Ing-Britt ; Ovesen, Jan: Muslim minorities in Cambodia